PERANCANGAN CORPORATE IDENTITY SEBAGAI MEDIA PROMOSI KAIN TENUN IKAT AFLAH JEPARA (Science and Technology (SciTech), 2022)
Aflah Ikat Weaving is a home industry which is located in Ds.Troso Rt.07/Rw.01 Pecangaan Jepara The increasing number of similar businesses makes the competition tighter. Aflah Ikat Weaving requires a corporate identity to become a hallmark of Aflah Ikat Weaving so that it can compete with other home industries. The formulation of the problem in designing this corporate identity is how to design Aflah Ikat Weaving as a promotional media, How to design a more effective promotional media design for Aflah Ikat Weaving. This design aims to design a more effective promotional media for Aflah Ikat Weaving Jepara.